Aromatization of Commercial Full Range Naphtha Over Modified Hierarchical ZSM‐5 Catalyst. Issue 42 (8th November 2021) - Ummer, Aniz Chennampilly; Akhtar, Muhammad Naseem; Alnaimi, Essa; Ding, Lianhui; Alasiri, Hassan Saeed
Abstract: Aromatization of commercial full range naphtha has been studied in a fixed bed reactor using the synthesized hierarchical zeolite catalysts. Desilication was carried out on H‐ZSM‐5 support with Silica to Alumina (SiO2 /Al2 O3 ) molar ratio 30 to generate additional meso‐porosity and active metal Gallium was incorporated by wetness impregnation method. Various concentrations of sodium hydroxide solutions and two different initial calcination temperature were used during the modification to understand the effect of these parameters on the catalysts. All the catalysts were characterized using nitrogen adsorption, X‐ray diffraction, temperature programmed ammonia desorption, elemental and surface imaging techniques. Catalytic evaluation is done in a fixed bed reactor operated at a temperature of 550 °C, atmospheric pressure and liquid hourly space velocity of 6.0 h −1 . Product streams from the fixed bed reactor are analyzed using both online and offline gas chromatographs using ASTM D7833 and D6729 respectively to report product selectivity and mass balance. It is observed that the additional meso porosity and the retention of crystallite phase lead to 62.4 % enhancement in aromatic selectivity and 52.2 % decrease in off‐gas generation for the developed catalyst compared to its non‐desilicated analogue during the aromatization process of full range real naphtha. Abstract : Efficient Ga/H‐ZSM‐5 catalyst has been prepared, characterized and evaluated for the aromatization of commercial naphtha feed at atmospheric pressure. The developed catalyst has improved meso porosity, tuned acidity and possesses higher hydrothermal stability to prevent structure sintering. This catalyst generated BTEX (benzene, toluene, ethyl benzene and xylene) containing liquid as major product and significantly reduced the formation of undesired off‐gases during the catalytic evaluation using fixed bed reactor. Products are analyzed using ASTM D7833 & D6729 and the conversion, yield and product selectivity are reported in detail.